2015
DOI: 10.56431/p-qzyv33
|View full text |Cite
|
Sign up to set email alerts
|

Ethnomedicinal and Conservation Status of Plant Species in Tehsil Takht Bhai, District Mardan, Pakistan

Abstract: The study was design to draw attention to correlation of locals with plants and their conservation status. The research work was carried out in tehsil Takht Bhai, district Mardan during 2008-2010. Fieldwork was conducted using an arrangement of interviews, questioners and personal observation. The IUCN 2001, Red Data List Categories and Criteria was used to determine the conservation status of plants. The present study documents the ethno medicinal and conservation status of 34 plant species belonging to 20 fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…From the 28 stands, floral and phytosociological data and relevant environmental factors, i.e., geographic attributes, soil texture, and nutrients, were data-banked for analysis and interpretation. Following the flowchart in Figure 2, various floristic attributes, i.e., life form, leaf form, status in Pakistan, and Rainkiaer life form, were assigned to species following already published literature conducted in areas that resemble the study area [40,41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the 28 stands, floral and phytosociological data and relevant environmental factors, i.e., geographic attributes, soil texture, and nutrients, were data-banked for analysis and interpretation. Following the flowchart in Figure 2, various floristic attributes, i.e., life form, leaf form, status in Pakistan, and Rainkiaer life form, were assigned to species following already published literature conducted in areas that resemble the study area [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…The means of the environmental and topographical factors were determined using a paired t-test to identify variances. utes, i.e., life form, leaf form, status in Pakistan, and Rainkiaer life form, were assigned to species following already published literature conducted in areas that resemble the study area [40,41]. The relative phytosociological qualities were converted into an importance value index (IVI).…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that majority of plants became extinct because of their high medicinal potential, over grazing, unwanted deforestation and other anthropogenic activities. This is also indicating that due to lack of basic life facilities, electric city and natural gas, the local communities totally depend on natural resources for timber, fuel and fodder purposes, made the plant resources endangered (Khan and Musharaf 2015).…”
Section: Conservation Status Of the Floramentioning
confidence: 99%
“…Other researchers such as (Farooq et al 2012;Ahmad at el. 2014;Khan and Musharaf 2015;Abbas et al 2016;Ali at el. 2017;Hussain at el.…”
Section: Introductionmentioning
confidence: 99%
“…and ornamental (10 spp.) (Khan et al 2015). It was also investigated that how the plantations of Eucalyptus play an important role in the economy of local communities of District Malakand.…”
Section: Introductionmentioning
confidence: 99%